Efficient deoxygenation of triglycerides to hydrocarbon-biofuel over mesoporous Al2O3-TiO2 catalyst - Ooi, Xian Yih; Oi, Lee Eng; Choo, Min Yee; Ong, Hwai Chyuan; Lee, Hwei Voon; Show, Pau Loke; Lin, Yu Chuan; Juan, Joon Ching (Elsevier, 2019)
The renewable hydrocarbon-like biofuel from biomass is crucial to substitute fossil fuel. A series of mesoporous Al2O3-TiO2 mixed oxide catalysts with different TiO2 content (0.1Ti-0.9Al, 0.2Ti-0.8Al and 0.3Ti-0.7Al) have been synthesized. The physicochemical properties of the catalysts were characterized by XRD, FESEM-EDX, BET, FTIR, NH3-TPD, FTIR-Py, and TGA. The deoxygenation (DO) of triglyceride (i.e. triolein) was carried out in the absence of hydrogen and solvent. The mesoporous Al2O3-TiO2 catalysts showed high catalytic activity performance as compared to that of Al2O3 and TiO2. It was found that 0.2Ti-0.8Al catalyst exhibited the highest conversion (76.86%), and selectivity (27.26%) toward n-C15 + n-C17 at 380 °C after 4 h. The excellence performance of mesoporous Al2O3-TiO2 was attributed to its acidity, mesoporosity and larger surface area. The results reveal that the mesoporous Al2O3-TiO2 catalyst is a promising catalyst for the synthesis of hydrocarbon-like biofuel. © 2019 Elsevier B.V.